MANIFESTO 'ENDOG ABANG' SEBAGAI STRATEGI POPULISME PARTAI UMMAT DALAM PEMILU 2024 - Iskandar, Iskandar; Paskarina, Caroline; Herdiansyah, Ari Ganjar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to analyze the relationship between populism theory and the Ummat Party, with a focus on political identity, anti-elite narratives, mass mobilization, and the programs offered by the party. The research also aims to understand the Ummat Party's strategic approach in dealing with the cultural regime and voicing criticism of the national regime. The object of this research is the Ummat Party, especially in the context of the Yogyakarta Special Region (DIY), with an emphasis on the Endog Abang Manifesto as a representation of the party's political ideology and strategy. The research method used is text and content analysis, by collecting and analyzing information from various sources such as speeches, manifestos, interviews and related literature. A qualitative approach is used to explore an in-depth understanding of the relationship between populism theory and the Ummat Party. The research results show that the Ummat Party uses populism theory as an ideological and strategic basis in mobilizing the masses, especially through Islamic political identity, anti-elite narratives, and offering programs that prioritize social and economic justice. The Endog Abang Manifesto became a symbol of this approach, combining local identity with the values of justice championed by the Ummat Party. This research concludes that the Ummat Party is a real example of the theory of populism in the Indonesian political context. They combine Islamic identity, criticism of political elites, mass mobilization, and the offer of programs focused on social and economic justice. The Ummat Party's strategic approach in dealing with the cultural regime also shows caution and consistency in voicing criticism and formulating desired changes in society.